2013
DOI: 10.1016/j.jamcollsurg.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and Antecedent Nonthyroidal Malignancies in Patients with Papillary Thyroid Carcinoma

Abstract: Background There is a known association between the development of papillary thyroid cancer (PTC) after a primary non-thyroidal cancer (NTC). However, the prevalence of synchronous or antecedent NTCs in patients with PTC is undetermined, as are the clinicopathologic characteristics of PTC in these patients. Study Design A review was performed of our prospectively maintained PTC database between January 1995 and December 2010. Information collected included patient and tumor characteristics, past medical hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Synchronous primary tumors are rare, however, epidemiological studies of multiple primary tumors are currently ongoing ( 1 5 ). A population-based retrospective cohort analysis conducted by Chen et al ( 2 ) identified that females with a history of thyroid carcinoma have an increased risk of developing BC, particularly premenopausal Caucasian females ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synchronous primary tumors are rare, however, epidemiological studies of multiple primary tumors are currently ongoing ( 1 5 ). A population-based retrospective cohort analysis conducted by Chen et al ( 2 ) identified that females with a history of thyroid carcinoma have an increased risk of developing BC, particularly premenopausal Caucasian females ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the above-mentioned literature, a history of thyroid carcinoma may increase the risk of BC. Furthermore, Murray et al ( 5 ) reported that BC was the most common type of primary non-thyroidal cancer associated with the subsequent development of PTC and that primary non-thyroidal cancer PTC patients presented at a more advanced stage. A previous study indicated that radiotherapy to treat cancer patients may increase the risk of developing a second malignancy ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were two population-based studies that reported incidence rather than risk-one reported on 8 individuals with TC after primary CM, and one reported on 7 individuals with CM after primary TC; these were excluded [3,4]. Characteristics of the included population-based studies are summarized in Table 1 Scotland (1975Scotland ( -1996.…”
Section: Resultsmentioning
confidence: 99%